(3TQM aJM GdHSGWs - (3eLghds ((3eMeO HgGA GdOjf GdLGHQi GdMSjfi s)
(3ChdgG (B:s
(3CeG HYO EPG SCdhc Yf NQbI GdfHi Udi Gddg Ydjg hSde GdLhGH CQHYI ChQGb ef ChQGb TLQI s
(3BNQgG (B:s
(3hjbQC GdaGJMI KdGK eQGJ MVQI GdfHi Udi Gddg Ydjg hSde gPG TQM aJM GdHSGW JeJ HYhf Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs